The Modern law review, vol.15 - Chorley, Robert Samuel Theodore Chorley, Baron, 1895-1978. (Oxford : Published for the Modern Law Review Ltd. by Basil Blackwell Ltd., 1952)
Includes section "Reviews."
Published: London, Stevens & Sons, 1937-1989.
Editor: June 1937- R. S. T. Chorley.
Index to legal periodicals
Legal resource index
Also available via World Wide Web
Vols. 1-33, 1937-75. 1 v.
Keywords: Law -- Great Britain -- Periodicals